Time and Education in Plato - Scolnicov, Samuel (2015)
This paper aims to present some views about Plato's reflection on education and its temporality, emphasizing the "inner" time involved in questions of areté, knowledge and teleology of human life. The dignity of living as an aim dependant on normative reason (lógos), is a base to the action of those who have Philosophy as an specific reflection for the education of the soul, as the Philosopher regarded it.